Dosimetric comparison of volumetric modulated arc therapy and three dimensional conformal radiotherapy in the adjuvant setting for the management of gastric cancer : target volume coverage and normal tissue sparing - Reddy, Bhiskar (Division of Radiology, 2015)
Includes bibliographical references.